THE MEMORY OF MOTHER IN DISNEY’S FAIRY TALE MOVIES - Indayanti, Pindy; Rosma Tami; Ahmad (UIN Alauddin Makassar, 2022)
This study discusses the memory to the mothers in Disney’s fairy tale movies. This study aimed to analyze the princesses’ remembrances to their mothers and the effects of those remembrances by using the nostalgia theory by Linda Hutcheon. Three Disney movies, Cinderella, Beauty and The Beast, and Frozen II were studied using descriptive qualitative methods. The result of this study shows that the princesses remember their mothers due to adversities faced in their lives, and this memory is accessed through several media such as mother’s words, the mother’s old dress, the Lullaby, and places. It is also found that those remembrances empower the princesses and have many positive and significant effects on the princesses’ life, such as drawing strength and motivation, knowing the truth, reconstructing their identity, and maintaining self-identity. This positive effect occurs when the princesses have positive perspectives on the memory to past events. It means that it may have a negative effect if the past was taken as trauma or negative events. Furthermore, even though the late mothers can no longer have an influence on their children, their influence remains in the memory of the princesses. Keywords: